Positron Emission Tomography–Driven Strategy in Advanced Hodgkin Lymphoma: Prolonged Follow-Up of the AHL2011 Phase III Lymphoma Study Association Study. Issue 10 (1st April 2022) - Casasnovas, René-Olivier; Bouabdallah, Reda; Brice, Pauline; Lazarovici, Julien; Ghesquieres, Hervé; Stamatoullas, Aspasia; Dupuis, Jehan; Gac, Anne-Claire; Gastinne, Thomas; Joly, Bertrand; Bouabdallah, Krimo; Nicolas-Virelizier, Emmanuelle; et al.
Abstract : PURPOSE: The AHL2011 study (ClinicalTrials.gov identifier: NCT01358747 ) demonstrated that a positron emission tomography (PET)-driven de-escalation strategy after two cycles of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone (BEACOPP) provides similar progression-free survival (PFS) and overall survival (OS) and reduces early toxicity compared with a nonmonitored standard treatment. Here, we report, with a prolonged follow-up, the final study results. METHODS: Patients with advanced Hodgkin lymphoma (stage III, IV, or IIB with mediastinum/thorax ratio > 0.33 or extranodal involvement) age 16-60 years were prospectively randomly assigned between 6 × BEACOPP and a PET-driven arm after 2 × BEACOPP delivering 4 × ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) in PET2– and 4 × BEACOPP in PET2+ patients. PET performed after four cycles of chemotherapy had to be negative to complete the planned treatment. RESULTS: In total, 823 patients were enrolled including 413 in the standard arm and 410 in the PET-driven arm. With a 67.2-month median follow-up, 5-year PFS (87.5% v 86.7%; hazard ratio [HR] = 1.07; 95% CI, 0.74 to 1.57; P = .67) and OS (97.7% in both arms; HR = 1.012; 95% CI, 0.50 to 2.10; P = .53) were similar in both randomization arms. In the whole cohort, full interim PET assessment predicted patients' 5-year PFS (92.3% in PET2–/PET4–, 75.4% [HR = 3.26; 95% CI, 18.3 to 5.77] in PET2+/PET4– and 46.5% [HR = 12.4; 95% CI, 7.31 to 19.51] in PET4+ patients, respectively; P < .0001) independent of international prognosis score. Five-year OS was also affected by interim PET results, and PET2+/PET4– patients (93.5%; HR = 3.3; 95% CI, 1.07 to 10.1; P = .036) and PET4+ patients (91.9%; HR = 3.756; 95% CI, 1.07 to 13.18; P = .038) had a significant lower OS than PET2–/PET4– patients (98.2%). Twenty-two patients (2.7%) developed a second primary malignancy, 13 (3.2%) and 9 (2.2%) in the standard and experimental arms, respectively. CONCLUSION: The extended follow-up confirms the continued efficacy and favorable safety of AHL2011 PET-driven strategy, which is noninferior to standard six cycles of BEACOPP. PET4 provides additional prognostic information to PET2 and allows identifying patients with particularly poor prognosis.